Effects of gossypol on human and monkey sperm motility in vitro - Sukumal Chongthammakun (2018)
The effects of gossypol acetic acid on human and monkey sperm motility in vitro were studied by using multiexposure photography technique. Human and monkey spermatozoa were inhibited by gossypol to different degrees. Monkey sperm were absolutely immotile within 15 min after 50 μM of gossypol was added, but motility of human spermatozoa was not completely suppressed by gossypol even at the highest concentration used and longest duration of exposure. © 1986.